Privire spre viitor - Farmaciile Veterinare - Costin Gheorghiu (Medicamentul Veterinar, 2023)
As in other industries, entrepreneurship in Veterinary Medicine has its say and a number of Veterinarians are building their own business by opening veterinary pharmacies. In this PPT, a brief presentation is made, starting from the history of the evolution of the Romanian veterinary school and up to the present day with the evolution of the Farmavet company and the more than 1800 pharmacies at this time. Modern trade has contributed to the efficiency of veterinary pharmacies by bringing a new concept through the development of the portfolio of supplements, food and accessories for animals. A plea is also made for supporting a healthy pre-entrepreneurial business environment in the field of veterinary medicine business and that veterinary pharmacies must be supported by the institutions of the Romanian state to ensure the population's access to the health and well-being of animals.